1990
DOI: 10.1016/0014-5793(90)80131-2
|View full text |Cite
|
Sign up to set email alerts
|

Heme maintains catalytically active structure of cytochrome P‐450

Abstract: Treatment of purified cytochrome P-450 LM2 and its liposome-bound form with hydrogen peroxide led to complete destruction of the P-450 heme. The apoenzyme thus produced could be reconstituted to catalytically active cytochrome P-450 by incubation with hemin, the reconstitution efficiency being 50% for the soluble enzyme and 80% for the liposome-bound enzyme. The removal of heme from the soluble hemoprotein resulted in a 3-fold decrease in the efficiency of its incorporation into sonicated liposomes. The conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
1
16
0
3
Order By: Relevance
“…Thus, our data make it evident that only the N-terminal sequence 1-20 of the cytochrome P-450 2B4 molecule is deeply embedded in the membrane or even penetrates the membrane. This conclusion is in agreement with results of the comprehensive proteolysis proteoliposomes containing cytochrome P-450 2B4 [33]. We found that only the N-terminal 21 -amino-acid fragment remained bound to the liposomes.…”
Section: Resultssupporting
confidence: 93%
“…Thus, our data make it evident that only the N-terminal sequence 1-20 of the cytochrome P-450 2B4 molecule is deeply embedded in the membrane or even penetrates the membrane. This conclusion is in agreement with results of the comprehensive proteolysis proteoliposomes containing cytochrome P-450 2B4 [33]. We found that only the N-terminal 21 -amino-acid fragment remained bound to the liposomes.…”
Section: Resultssupporting
confidence: 93%
“…Destruction of the porphyrin ring by H 2 O 2 is known as an efficient and gentle approach to deplete cytochromes P450 completely of the heme group [38, 53, 54]. Therefore, in order to estimate the efficiency of FRET from BODIPY to the heme chromophore we employed the heme depletion (bleaching) of CYP3A4(C468)-BODIPY in the presence of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Removal of the heme from CYP3A4 and preparation of the apo-protein was performed by treatment with H 2 O 2 (Uvarov et al, 1990;Pikuleva et al, 1992). We implemented very mild conditions of treatment to prevent any peroxidative damage of the protein.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of the kinetics of CYP3A4 heme depletion in the presence of H 2 O 2 was done using conditions similar to those previously described (Uvarov et al, 1990;Pikuleva et al, 1992). The reaction was carried out at 25°C in 100 mM Hepes buffer, pH 7.4, in a 1-ml semi-microspectrophotometric cell with constant stirring.…”
Section: Methodsmentioning
confidence: 99%